Pengaruh Perencanaan dan Sumber Daya Manusia dalam Meningkatkan Serapan Anggaran di Kementerian Agama pada Masa Pandemi Covid-19 - Karbila, Ibnu Hasan; Sunaryo, Agus (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2022)
Absorption of the government's budget is one of the instruments for national economic recovery (PEN) during the COVID-19 pandemic. Proportionate budget absorption is able to increase consumption power and have an impact on people's welfare, this of course must be supported by quality planning and professional Human Resources. The budget absorption at the Ministry of Religion at the end of the year was included in the good category, but the lack of proportionate absorption every quarter was possible due to many factors including planning and human resources. The purpose of this study was to determine the effect of budget planning and human resources on budget absorption in the ministry of religion. Research method with quantitative multivariate correlation. Collecting data through a questionnaire by taking data on planning, human resources and budget absorption in 2020. The data was then analyzed using multiple linear regression analysis with the help of Partial Least Square (PLS). The results of the study show that the planning process and human resources at the Ministry of Religion are categorized as good. These two variables have an effect of 43.6% on budget absorption, while the other 56.4% are influenced by other factors not discussed in this study. This shows that planning and human resources are two inseparable variables and need attention in improving the quality of budget absorption during the pandemic.